Physical map of human Xq27-qter: localizing the region of the fragile X mutation. - Poustka, A (1991)
We describe a physical map of the end of the long arm of the human X chromosome encompassing the region from Xq27.2 to the q telomere, inclusive of the chromosomal band Xq28. This region is of particular interest, since it contains the highest density of genes associated with genetic diseases. The map covers a total of 12 megabases (Mb) of DNA and extends from the telomere to 3 Mb beyond the most likely position of the fragile X mutation, defined by a cluster of translocation breakpoints in somatic cell hybrids. The map determines order and position of loci throughout the Xq28 region and localizes cell line breakpoints marking the fragile X region to an interval of 300-700 kilobases between 8 and 8.7 Mb proximal of the Xq telomere.